ИНСТИТУЦИОНАЛЬНЫЕ ИНВЕСТОРЫ НА РЫНКЕ ЦЕННЫХ БУМАГ КАЗАХСТАНА (Journal of Economic Research & Business Administration, 2015)
The article considers the main aspects of the activity and funchoming of the institutional investors. There are emphasized seatures of the investment activity of the PF and insurance companies as main centers of capital accumulation. There are revealed the main problems of the institutional investors developments.